Spring Barley Cost-Return Budget (W-B-F Rotation) in Western Kansas - Sartwelle III, James D.; Thompson, Curtis R.; O'Brien, Daniel M. (My University, 1997)
This publications provides information on yield goals, variable and fixed costs, and profit and return factors for producing spring barley.
MF2097_1997_10
Keywords: MF2097; Crops; Economics; MF